Association of Perioperative Nursing Care with Incidence of Surgical Site Infections and Short-Term Outcomes in Primary Liver Cancer Patients: A Retrospective Comparison with Standard Care - Yang B; Guo X; Qi K; Sun S (Therapeutics and Clinical Risk Management)
Bin Yang,1 Xiaoyun Guo,1 Kewen Qi,1 Shaolong Sun2 1Department of Operating Room, Shengjing Hospital of China Medical University, Shenyang, Liaoning, 110004, People’s Republic of China; 2Department of General Surgery,Shengjing Hospital of China Medical University, Shenyang, Liaoning, 110004, People’s Republic of ChinaCorrespondence: Shaolong Sun, Department of General Surgery, Shengjing Hospital of China Medical University, No. 36, Sanhao Street, Shenyang, Liaoning, 110004, People’s Republic of China, Tel +86-024-96615-68801, Email sunsl@sj-hospital.orgBackground: Surgical site infections (SSIs) are a significant complication following liver surgery (LS) for primary liver cancer (PLC), contributing to increased morbidity, prolonged hospital stays, and higher healthcare costs. This study aimed to evaluate the association of perioperative nursing care (PNC) with the incidence of SSIs and short-term outcomes, comparing patients receiving structured PNC to those receiving standard care.Methods: A retrospective study was conducted at [specific location] between January 2016 and February 2019. A total of 360 PLC patients undergoing LS were included and divided into an observation group (PNC) and a control group (standard care). Outcome measures included SSI incidence, length of hospital stay, and independent predictors of SSIs. Logistic regression analysis was used to identify significant factors.Results: Among the 360 included PLC patients, 180 received PNC while 180 did not. Patients in the PLC group had a significantly lower incidence of SSIs (28.3% vs 47.2%, P = 0.026) and shorter hospital stays (median: 8.2 vs 13.3 days, P = 0.049) compared to the control group. Multivariate logistic regression identified PNC as a significant protective factor against SSIs (OR = 2.01, 95% CI: 1.08– 3.85, P = 0.031). Other significant predictors included education level (college or above: OR = 0.44, 95% CI: 0.24– 0.79, P = 0.006) and comorbidities (more than two: OR = 2.21, 95% CI: 1.31– 3.76, P = 0.003).Conclusion: PNC emerged as an independent risk factor for SSIs in PLC patients undergoing LS. Thus, the provision of PNC is crucial for reducing the risk of SSIs and improving short-term outcomes in PLC patients undergoing LS.Keywords: perioperative nursing care, PNC, surgical site infections, SSIs, primary liver cancer, PLC, liver surgery, LS